PVA-alkali lignin-based carbon aerogel as well as preparation method and application thereof

By using soluble nickel salts to adjust the pore structure and conductivity in the preparation of carbon aerogel, the problem of poor controllability of the electromagnetic shielding performance adjustment of carbon aerogel is solved, and its electromagnetic shielding performance is significantly improved.

CN119241242AActive Publication Date: 2025-01-03ZHEJIANG FORESTRY UNIVERSITY

Patent Information

Application Number
CN202411270576.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-03
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

The existing carbon aerogels have poor controllability in adjusting electromagnetic shielding performance and are insufficient in conductivity, which affects their electromagnetic shielding performance.

Method used

In the preparation process of aerogel, soluble nickel salt is added, and the hydroxyl groups of PVA and alkali lignin are formed through the nickel salt to form chelation, adjust the pore structure of the carbon aerogel, and convert the nickel salt into nickel nanoparticles through high-temperature carbonization. It is evenly dispersed inside the carbon aerogel to improve the conductivity of the electrical and magnetic conductivity.

Benefits of technology

The high electromagnetic shielding performance of carbon aerogel is achieved, and by adjusting the pore structure and conductivity, its electromagnetic shielding performance is significantly improved to reach the best state.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241242A_ABST
    Figure CN119241242A_ABST
Patent Text Reader

Abstract

The invention discloses PVA (polyvinyl alcohol) and alkali lignin-based carbon aerogel and a preparation method and application thereof.Soluble nickel salt is added in the aerogel preparation process, Ni < 2 + > and hydroxyl groups of PVA and AL (alkali lignin) form a chelation effect, the pore structure of the carbon aerogel is adjusted by adjusting the adding amount of the soluble nickel salt, and the porosity of the carbon aerogel is adjusted by adjusting the adding amount of the soluble nickel salt; the prepared carbon aerogel has a more developed and richer pore structure, so that the electromagnetic shielding effectiveness of the carbon aerogel reaches an optimal state, in addition, soluble nickel salt is converted into nickel nanoparticles after high-temperature carbonization, and the nickel nanoparticles are uniformly dispersed in the carbon aerogel, so that the conductivity and magnetic conductivity of the carbon aerogel are also favorably improved, and the electromagnetic shielding performance of the carbon aerogel is improved. Therefore, the electromagnetic shielding effectiveness of the carbon aerogel is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aerogel materials, and in particular to a PVA@alkali lignin-based carbon aerogel and a preparation method and application thereof. Background Art

[0002] With the rapid development of communication technology and the upgrading of electronic equipment, while it has brought convenience to our lives and work, it has also caused electromagnetic radiation pollution problems, which not only interferes with the normal operation of electronic equipment, but also affects human health, causing poor sleep quality, electromagnetic wave allergies and other discomforts, and even induces cancer. Therefore, the development of high-performance electromagnetic shielding materials has become a current research hotspot.

[0003] At present, common electromagnetic shielding materials mainly include metal materials, polymer conductive materials, etc. Among them, metal materials are the most common electromagnetic shielding materials. Their superior conductivity makes the materials have good electromagnetic shielding performance, but they also have problems such as heavy weight, easy corrosion, and easy to cause secondary pollution of electromagnetic waves. Polymer conductive materials are a new type of electromagnetic shielding composite material that is expected to replace metal materials by adding conductive fillers such as metal particles or carbon to synergistically construct a conductive network. Common structures include membrane structures, foam structures, aerogel structures, etc. In order to improve the conductivity of polymer conductive materials, it is usually achieved by increasing the amount of conductive fillers added. However, high filling of fillers will seriously affect the processability, mechanical properties and mixing uniformity of the composite material.

[0004] Based on this, some researchers have made carbon aerogels by high-temperature carbonization, which makes the aerogels conductive under high-temperature pyrolysis without adding any conductive fillers. Carbon aerogels are considered to be a highly promising and efficient electromagnetic shielding material due to their unique three-dimensional controllable structure, excellent conductivity and good chemical stability. In the preparation process of existing carbon aerogels, the directional regulation of the pore structure is usually achieved by adjusting the raw material ratio, molding method, etc. The developed pore structure helps electromagnetic waves to be reflected, scattered and absorbed multiple times inside the carbon aerogel. However, the above-mentioned method of regulating the internal pore structure of carbon aerogels has limited effect on the electromagnetic shielding effectiveness of carbon aerogels, and the controllability of the above-mentioned regulation process is poor. Summary of the invention

[0005] In order to solve the problems existing in the above-mentioned background technology, the present invention provides a PVA@alkali lignin-based carbon aerogel and a preparation method and application thereof. In the process of preparing the aerogel, a soluble nickel salt is added. Ni 2+By forming a chelate effect with the hydroxyl groups of PVA (polyvinyl alcohol) and AL (alkali lignin), the pore structure of the carbon aerogel is adjusted by adjusting the amount of soluble nickel salt added. The obtained carbon aerogel has a more developed and richer pore structure, so that the electromagnetic shielding performance of the carbon aerogel reaches the best state. In addition, the soluble nickel salt is converted into nickel nanoparticles after high-temperature carbonization, which are evenly dispersed inside the carbon aerogel, which also helps to improve the electrical and magnetic properties of the carbon aerogel, thereby further improving the electromagnetic shielding performance of the carbon aerogel.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The first aspect of the present invention provides a PVA@alkali lignin-based carbon aerogel, comprising the following raw material components:

[0008] Alkali lignin, polyvinyl alcohol, soluble nickel salt, water;

[0009] Among them, the mass ratio of alkali lignin to polyvinyl alcohol is (1-2):1, the mass ratio of alkali lignin to water is 1:(40-60), and the mass ratio of soluble nickel salt to water is (0-4):300.

[0010] Furthermore, the mass ratio of the soluble nickel salt to water is (0-2):300.

[0011] Furthermore, the mass ratio of the soluble nickel salt to water is (0-1):300. More preferably, the mass ratio of the soluble nickel salt to water is 0.5:300.

[0012] Furthermore, the soluble nickel salt is NiCl2·6H2O or NiSO4·7H2O.

[0013] Furthermore, the PVA@alkali lignin-based carbon aerogel has a tubular pore structure inside.

[0014] The second aspect of the present invention provides a method for preparing the above-mentioned PVA@alkali lignin-based carbon aerogel, comprising the following steps:

[0015] S1. Add alkali lignin into water and stir to mix evenly;

[0016] S2, adding polyvinyl alcohol and soluble nickel salt to the solution obtained in step S1, stirring and mixing well, and then pouring the mixture into a mold;

[0017] S3, freeze-drying the mold and the contents in step S2, and obtaining an aerogel after demoulding;

[0018] S4, placing the aerogel obtained in step S3 in an inert gas atmosphere for carbonization to obtain PVA@alkali lignin-based carbon aerogel.

[0019] Furthermore, in step S3, the freeze-drying process includes directional freezing and drying.

[0020] Freeze drying refers to a drying method in which a water-containing material is frozen below the freezing point, the water is converted into ice, and then the ice is converted into vapor under a relatively high vacuum and removed.

[0021] In the present invention, a directional freezing method is preferably used. During the directional freezing process, ice crystals grow slowly in a specific direction (such as from bottom to top), so that the interior of the aerogel has an obvious tubular structure.

[0022] Furthermore, in step S4, the ventilation volume of the inert gas is 200-400 mL / min, and the carbonization process is: heating to 900-1100° C. at a heating rate of 1-5° C. / min, and keeping warm for 1-2 hours.

[0023] During the carbonization process, soluble nickel salts are reduced at high temperature to obtain Ni nanoparticles, which are evenly dispersed inside the carbon aerogel. Moreover, by controlling the carbonization conditions (heating rate, carbonization temperature and holding time), the carbon aerogel retains the original tubular structure of the aerogel, and the carbon aerogel has a good graphitization effect.

[0024] Furthermore, in step S2, the solution obtained in step S1 is first heated and controlled at 80-95° C., and then polyvinyl alcohol and soluble nickel salt are added thereto.

[0025] Under the above temperature conditions, polyvinyl alcohol and alkali lignin undergo a cross-linking reaction to form a cross-linked network structure.

[0026] The third aspect of the present invention provides an application of the above-mentioned PVA@alkali lignin-based carbon aerogel in electromagnetic shielding materials and electrothermal conversion materials.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) In the present invention, alkali lignin (AL) is used as a carbon precursor and polyvinyl alcohol (PVA) is used as a long-chain structure. There are a large number of hydroxyl groups in alkali lignin and polyvinyl alcohol, so that different types of intermolecular hydrogen bonds and van der Waals forces are formed between alkali lignin and polyvinyl alcohol, and between polyvinyl alcohol and polyvinyl alcohol. Polyvinyl alcohol connects alkali lignin in series through hydrogen bonds. Through directional freeze drying and high-temperature carbonization, the polyvinyl alcohol molecular chain is carbonized and condensed, shortening the distance between alkali lignin carbons, increasing the contact area between alkali lignin carbon particles, and improving the conductivity of carbon aerogel, thereby preparing carbon aerogel with high electromagnetic shielding effectiveness;

[0029] (2) In order to adjust the pore structure of carbon aerogel, soluble nickel salt is added during the preparation of aerogel.2+ It forms a chelating effect (coordination bond) with the hydroxyl groups of alkali lignin and polyvinyl alcohol, and plays a cross-linking role in the whole system. 2+ Effectively and evenly anchored on polyvinyl alcohol and alkali lignin, the pore structure of carbon aerogel is adjusted by adjusting the amount of soluble nickel salt added, so that the electromagnetic shielding performance of carbon aerogel reaches the best state. In addition, the soluble nickel salt is converted into nickel nanoparticles after high-temperature carbonization, which also helps the electrical and magnetic properties of aerogel and improves the electromagnetic shielding performance of carbon aerogel.

[0030] (3) Aerogels are prepared by directional freezing and drying. During the directional freezing process, ice crystals grow slowly in a specific direction, so that the aerogels have a distinct tubular structure, and the alkali lignin is evenly embedded in the tube wall structure;

[0031] (4) During the carbonization process, by controlling the carbonization conditions (heating rate, carbonization temperature and holding time), the carbon aerogel retains the original tubular structure of the aerogel and has a good graphitization effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0033] Figure 1 Schematic diagram of the formation mechanism of carbon aerogel CAPNix in the present invention;

[0034] Figure 2 The scanning electron microscope image (ai) of the carbon aerogel sample CAPNix in the present invention, CAPNi 0.5 EDS energy spectra of C, O and Ni (i1-i3).

[0035] Figure 3 The results of the physical characterization and identification of the carbon aerogel sample CAPNix in the present invention are shown in Figure 1. a is the Fourier infrared spectrum test diagram; b is the XPS spectrum; c is the content of C and O in the sample; d is the CAPNi 0.5 The spectrum of C1s in the graph; e is CAPNi 0.5 Medium to high resolution Ni 2p spectrum; f is the Raman spectrum; g is the hysteresis loop; h is the N2 adsorption-desorption isotherm; i is the pore size distribution diagram.

[0036] Figure 4 This is a test diagram of the electromagnetic interference shielding effect of the carbon aerogel sample CAPNix in the present invention.

[0037] Figure 5 Schematic diagram of the electromagnetic shielding mechanism of the carbon aerogel sample CAPNix in the present invention.

[0038] Figure 6This is a Joule heating performance test diagram of the carbon aerogel sample CAPNix in the present invention.

[0039] Figure 7 A test diagram of the Tesla coil demonstrating electromagnetic shielding experiment. DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Main experimental materials in each embodiment:

[0042] NiCl2·6H2O, NiSO4·7H2O, and polyvinyl alcohol were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0043] Alkali lignin was purchased from Shanghai Yixing Technology Co., Ltd.

[0044] Deionized water is collected from a water purification system.

[0045] Experimental characterization:

[0046] The morphology of the samples was observed using a field emission scanning electron microscope (SEM, Hitachi SU 8010, Japan).

[0047] Raman spectroscopy (Raman, Horiba LabRAM HR Evolution, Japan) was used to characterize the carbon aerogels.

[0048] X-ray electron spectroscopy (XPS, Thermo Scientific K-Alpha, USA) was used to analyze the chemical structure and elements of the samples.

[0049] The chemical groups were observed using FT-IR spectrometer (Nicolet iS20, USA) with a wave number range of 4000–400 cm -1 .

[0050] The electrical conductivity of the samples was obtained by a four-point probe method (Suzhou Jingge Electronics, ST2258C, China).

[0051] The specific surface area (SSA), pore volume, and size distribution were determined using an automated adsorption system (ASAP2420, Micromeritics, USA) with the Brunauer-Emmet-Teller (BET) equation of nitrogen physical adsorption at 77 K.

[0052] A vibrating sample magnetometer (VSM, Lakeshore 8604, USA) was used to characterize the magnetic properties of the samples.

[0053] The samples were analyzed by a vector network analyzer (Agilent Technologies E5071C, USA) to determine the EMI shielding effect. The waveguide rectangular area was pre-cut into 22.86 mm × 10.16 mm strips to match the support (8.2-12.4 GHz).

[0054] Deduced from the law of conservation of energy, the reflection coefficient R, absorption coefficient A, and transmission coefficient T can be expressed as formula (1):

[0055] R+A+T=1

[0056] R=|S 11 | 2 =|S 22 | 2

[0057] T=|S 12 | 2 =|S 21 | 2

[0058] In the formula, S 11 is the reflection coefficient, S 21 is the transmission coefficient. The total electromagnetic interference shielding effectiveness (SET) generally consists of three parts, namely the reflection efficiency (SER) of the material surface, the absorption efficiency (SEA) of the magnetic permeability loss on the material surface, and the multiple reflection efficiency (SEMR) inside the material. When SET is higher than 15dB, SEMR can be technically ignored. SER and SEA can be calculated by formula (2):

[0059]

[0060] SE T =SE R +SE A .

[0061] Examples 1-5

[0062] The preparation method of PVA@alkali lignin-based carbon aerogel comprises the following steps:

[0063] S1. Slowly add 6 g of alkali lignin into 300 g of deionized water and stir and mix under magnetic stirring for 3 h;

[0064] S2, placing the solution obtained in step S1 in an oil bath at 90°C and heating it, slowly adding 4.5g of polyvinyl alcohol and a certain amount of NiCl2·6H2O thereto, and pouring it into a round mold after being fully stirred and dissolved;

[0065] S3, performing liquid nitrogen directional freezing on the mold in step S2, first placing the shelf in liquid nitrogen, and then placing the circular mold on the shelf frozen by liquid nitrogen, the ice crystals formed in the content of the circular mold slowly grow from bottom to top, and then vacuum drying, the ice crystals are directly converted into steam and removed, to obtain an aerogel, the aerogel has a clear tubular pore structure, and the alkali lignin is uniformly embedded in the tube wall structure;

[0066] In Example 1, NiCl2·6H2O was not added, and in step S3, the aerogel obtained was recorded as AAP;

[0067] In Example 2, 0.5 g NiCl2·6H2O was added, and in step S3, the aerogel obtained was recorded as AAPNi 0.5 ;

[0068] In Example 3, 1 g of NiCl2·6H2O was added, and in step S3, the aerogel obtained was recorded as AAPNi1;

[0069] In Example 4, 1.5 g NiCl2·6H2O was added, and in step S3, the aerogel obtained was recorded as AAPNi 1.5 ;

[0070] In Example 5, 2 g NiCl2·6H2O was added, and in step S3, the aerogel obtained was recorded as AAPNi2;

[0071] S4, placing the aerogel obtained in step S3 in a tubular furnace, introducing nitrogen at a ventilation rate of 300 mL / min, heating to 1100°C at a rate of 2.5°C / min, keeping the temperature for 1 hour and then naturally cooling to room temperature. The carbon aerogels obtained in Examples 1-5 are respectively denoted as CAP, CAPNi 0.5 , CAPNi1, CAPNi 1.5 、CAPNi2.

[0072] Example 6

[0073] The preparation method of PVA@alkali lignin-based carbon aerogel comprises the following steps:

[0074] S1. Slowly add 4.5 g of alkali lignin into 180 g of deionized water, and stir and mix under magnetic stirring for 3 h;

[0075] S2, placing the solution obtained in step S1 in an oil bath at 95°C and heating it, slowly adding 4.5g polyvinyl alcohol and 1.8g NiCl2·6H2O thereto, and pouring into a round mold after being fully stirred and dissolved;

[0076] S3, performing liquid nitrogen directional freezing on the mold in step S2, first placing the shelf in liquid nitrogen, and then placing the circular mold on the shelf frozen by liquid nitrogen, the ice crystals formed in the content of the circular mold slowly grow from bottom to top, and then vacuum drying, the ice crystals are directly converted into steam and removed, to obtain an aerogel, the aerogel has a clear tubular pore structure, and the alkali lignin is uniformly embedded in the tube wall structure;

[0077] S4. The aerogel obtained in step S3 was placed in a tubular furnace, nitrogen was introduced at a flow rate of 200 mL / min, the temperature was raised to 1100° C. at a rate of 3° C. / min, and the aerogel was naturally cooled to room temperature after being kept at this temperature for 1 h to obtain a carbon aerogel.

[0078] Example 7

[0079] The preparation method of PVA@alkali lignin-based carbon aerogel comprises the following steps:

[0080] S1. Slowly add 9 g of alkali lignin into 540 g of deionized water and stir and mix under magnetic stirring for 3 h;

[0081] S2, placing the solution obtained in step S1 in an oil bath at 80°C and heating it, slowly adding 4.5g polyvinyl alcohol and 7.2g NiCl2·6H2O thereto, and pouring into a round mold after being fully stirred and dissolved;

[0082] S3, performing liquid nitrogen directional freezing on the mold in step S2, first placing the shelf in liquid nitrogen, and then placing the circular mold on the shelf frozen by liquid nitrogen, the ice crystals formed in the content of the circular mold slowly grow from bottom to top, and then vacuum drying, the ice crystals are directly converted into steam and removed, to obtain an aerogel, the aerogel has a clear tubular pore structure, and the alkali lignin is uniformly embedded in the tube wall structure;

[0083] S4. The aerogel obtained in step S3 was placed in a tubular furnace, nitrogen was introduced at a flow rate of 400 mL / min, the temperature was raised to 900°C at a rate of 1°C / min, and the aerogel was naturally cooled to room temperature after being kept at this temperature for 2 h to obtain a carbon aerogel.

[0084] Example 8

[0085] The preparation method of PVA@alkali lignin-based carbon aerogel comprises the following steps:

[0086] S1. Slowly add 6 g of alkali lignin into 300 g of deionized water and stir and mix under magnetic stirring for 3 h;

[0087] S2, placing the solution obtained in step S1 in an oil bath at 80°C and heating it, slowly adding 4.5g polyvinyl alcohol and 0.5g NiSO4·7H2O thereto, and pouring it into a round mold after being fully stirred and dissolved;

[0088] S3, performing liquid nitrogen directional freezing on the mold in step S2, first placing the shelf in liquid nitrogen, and then placing the circular mold on the shelf frozen by liquid nitrogen, the ice crystals formed in the content of the circular mold slowly grow from bottom to top, and then vacuum drying, the ice crystals are directly converted into steam and removed, to obtain an aerogel, the aerogel has a clear tubular pore structure, and the alkali lignin is uniformly embedded in the tube wall structure;

[0089] S4. The aerogel obtained in step S3 was placed in a tubular furnace, nitrogen was introduced at a flow rate of 300 mL / min, the temperature was raised to 1100° C. at a rate of 5° C. / min, and the mixture was kept at this temperature for 1.5 h and then naturally cooled to room temperature to obtain carbon aerogel.

[0090] Example 9

[0091] The preparation method of PVA@alkali lignin-based carbon aerogel comprises the following steps:

[0092] S1. Slowly add 6 g of alkali lignin into 300 g of deionized water and stir and mix under magnetic stirring for 3 h;

[0093] S2, placing the solution obtained in step S1 in an oil bath at 90°C and heating it, slowly adding 4.5g polyvinyl alcohol and 0.5g NiCl2·6H2O thereto, and pouring it into a round mold after being fully stirred and dissolved;

[0094] S3, performing liquid nitrogen directional freezing on the mold in step S2, first placing the shelf in liquid nitrogen, and then placing the circular mold on the shelf frozen by liquid nitrogen, the ice crystals formed in the content of the circular mold slowly grow from bottom to top, and then vacuum drying, the ice crystals are directly converted into steam and removed, to obtain an aerogel, the aerogel has a clear tubular pore structure, and the alkali lignin is uniformly embedded in the tube wall structure;

[0095] S4. The aerogel obtained in step S3 was placed in a tubular furnace, nitrogen was introduced at a flow rate of 300 mL / min, the temperature was raised to 1100° C. at a rate of 2.5° C. / min, and the mixture was kept at that temperature for 1 h and then naturally cooled to room temperature to obtain carbon aerogel.

[0096] Experimental test results:

[0097] The preparation of carbon aerogel includes two steps: freeze drying and carbonization pyrolysis. Its formation mechanism is as follows Figure 1 shown.

[0098] Polyvinyl alcohol, alkali lignin and soluble nickel salt are dissolved in deionized water to form a uniform and stable mixed system. Polyvinyl alcohol and alkali lignin have a large number of hydroxyl groups, which form different types of intermolecular hydrogen bonds and van der Waals forces between polyvinyl alcohol and alkali lignin, and between polyvinyl alcohol and polyvinyl alcohol. In addition, Ni 2+ It can form coordination bonds with the hydroxyl groups of polyvinyl alcohol and alkali lignin, playing a cross-linking role in the whole system. 2+ Effectively and uniformly anchored on polyvinyl alcohol and alkali lignin.

[0099] Subsequently, the mixture was poured into a circular mold and directionally frozen and dried with liquid nitrogen to produce the aerogel AAPNix. During the directional freezing process, ice crystals grew slowly in a specific direction, giving the aerogel a distinct tubular structure, with alkali lignin evenly embedded in the tube wall structure.

[0100] The obtained aerogel is carbonized at high temperature in a tubular furnace to obtain carbon aerogel CAPNix. The soluble nickel salt is reduced at high temperature to obtain Ni nanoparticles, which are evenly dispersed inside the carbon aerogel, helping to improve the electrical and magnetic properties of the carbon aerogel, thereby further improving the electromagnetic shielding effectiveness of the carbon aerogel.

[0101] 1. Morphological analysis of the prepared samples

[0102] Figure 2 SEM images of the samples (ai), CAPNi 0.5 EDS energy spectra of C, O and Ni (i1-i3).

[0103] Figure 2 a is a front cross-sectional view of aerogel AAP. It can be seen from the figure that the aerogel has an obvious tubular structure. This is because during the formation and directional growth of ice crystals, polyvinyl alcohol and alkali lignin are repelled by the ice crystals, forming a directional structure along the growth direction of the ice crystals. Figure 2 b is a partial enlarged view of 2a. Due to the good film-forming properties of polyvinyl alcohol, the vessel wall has an obvious transverse diaphragm structure, and there are only a few pore structures on the vessel wall. In addition, the surface of the vessel wall is relatively smooth, indicating that alkali lignin and Ni 2+ It is evenly distributed inside PVA because PVA, AL and NiCl2 can form a uniform solution after dissolving in water.

[0104] Figure 2c is the carbon aerogel CAP obtained by carbonizing aerogel AAP at 1100°C. By comparing 2a and 2b, it is found that the carbon aerogel retains the original tubular structure of the aerogel. However, the tubular structure shows obvious shrinkage, and the bulges on the surface of the pore wall become denser. The main reason is that the long-chain molecules of polyvinyl alcohol show obvious shrinkage after high-temperature carbonization, which makes the alkali lignin carbon particles and Ni nanoparticles in closer contact under the action of polyvinyl alcohol.

[0105] Figure 2 c to 2g are the front cross-sectional views of carbon aerogel CAPNix with different nickel addition amounts. As the Ni content increases, the pore diameter of the carbon aerogel gradually increases. The reason is that polyvinyl alcohol, alkali lignin and Ni 2+ The organic-inorganic cross-linked network weakens the aggregation phenomenon of aerogel after carbonization.

[0106] Figure 2 i1-i3 are carbon aerogel CAPNi 0.5 The EDS graphs of C, O, and Ni show that the C element accounts for the largest proportion in the carbon aerogel, and only a small amount of O element exists after high-temperature carbonization. In addition, the Ni element is evenly distributed, which helps to improve the electrical conductivity and magnetic permeability of the carbon aerogel, thereby improving the electromagnetic shielding effectiveness.

[0107] 2. Phase Characterization and Identification of Prepared Samples

[0108] Figure 3 The results of the phase characterization and identification of the samples are shown in Figure 2. Figure 3 a) Fourier transform infrared spectra of aerogel AAP and carbon aerogel CAPNix, respectively. The aerogel AAP has a wavelength of 3415 cm -1 There is a wide band around 2939cm, which is caused by the stretching vibration of -OH. These characteristic peaks are attributed to the phenolic hydroxyl groups of alkali lignin, lignin and polyvinyl alcohol aliphatic hydroxyl groups in aerogel. -1 and 1456cm -1 1600cm-1 is the -CH stretching vibration peak and deformation vibration peak of the methoxy, methyl and methylene groups in the aerogel. -1 、1512cm -1 The -OH stretching vibration peak of each carbon aerogel is significantly weakened after high-temperature carbonization, and the peak at 2939cm -1 and 1456cm -1 The -CH stretching vibration peak and deformation vibration peak at 1634cm -1 The C=C at the carbon aerogel indicates that a small amount of aromatic ring structure is still retained in the carbon aerogel.

[0109] Figure 3b shows the XPS spectrum of carbon aerogel CAPNix. Except for sample CAP, the other four samples have four characteristic peaks, namely C1s, O 1s, Ni 2p, and Na 1s. Among them, the C1s characteristic peak is significantly higher than the other characteristic peaks, and the atomic content is not less than 90% ( Figure 3 c). The test results show that Na 1s exists in the carbon aerogel, which is due to the presence of sodium salt in the alkali lignin raw material. In addition, a weak Ni 2p characteristic peak can be found in the carbon aerogel CAPNix, indicating that nickel nanoparticles have been successfully loaded into the carbon aerogel.

[0110] Figure 3 d is the high-resolution C1s spectrum, the peak of CC / C=C (284 eV) is strong, while the peaks of CO (285.2 eV) and OC=O (289.3 eV) are relatively weak, indicating that most of the carbon species in the carbon aerogel belong to the sp2 conjugated carbon skeleton. Figure 3 e shows the high-resolution Ni 2p spectrum. Peak fitting shows that nickel exists in two main states, namely Ni (852.8 eV) and Ni 2+ (855.6eV), of which Ni 2+ The characteristic peak is larger than Ni, indicating that the content of nickel compounds is more than metallic Ni.

[0111] Figure 3 f is the Raman spectrum of carbon aerogel CAPNix. In the figure, D band (~1350cm -1 ) and G band (~1580cm -1 ), the D band is related to the structural defects or disorder caused by the presence of sp3 hybridized carbon atoms, reflecting the degree of disorder, while the formation of the G band is due to the vibration of the sp2 hybridized bonds in the hexagonal lattice of graphitic carbon, reflecting the degree of order. The ratio of ID to IG is used to indicate the degree of graphitization of the sample. The smaller the ID / IG, the better the graphitization degree of the carbon aerogel.

[0112] When the nickel content is zero, the carbon aerogel CAP has the minimum ID / IG ratio of 0.933. As the nickel content increases, the ID / IG ratio of the carbon aerogel CAPNix gradually increases, indicating that the degree of graphitization of the carbon aerogel gradually decreases with the increase of nickel content. The possible reason is that the carbon aerogel skeleton gradually increases with the increase of nickel content, which is conducive to the overflow of CO and CO2 gases in the carbon aerogel during high temperature. The gas overflow promotes the formation of pore structure, resulting in structural defects that reduce the degree of graphitization. This is consistent with the changes in oxygen elements measured in XPS ( Figure 3c), as the nickel content increases, the oxygen content of the carbon aerogel gradually decreases and the carbon content gradually increases. Although the ID / IG of the carbon aerogel CAPNix decreases slightly with the increase of nickel content, it still has a better graphitization effect than other materials.

[0113] Figure 3 g is the hysteresis loop of carbon aerogel CAPNix prepared with different nickel addition amounts. Through the analysis of the hysteresis loop, it is found that the saturation magnetization of CAPNix increases with the increase of NiCl2·6H2O concentration, which are -0.05emu / g, 0.31emu / g, 0.93emu / g, 1.59emu / g, and 2.48emu / g, respectively, indicating that the magnetism of carbon aerogel CAPNix increases with the increase of nickel ion concentration. This is because there are more nickel nanoparticles on the carbon aerogel skeleton, which helps to improve the magnetic loss capacity of carbon aerogel CAPNix to electromagnetic waves.

[0114] Figure 3 h shows that the N2 adsorption-desorption isotherm of carbon aerogel CAPNix is ​​consistent with the IV type isotherm adsorption curve (IUPAC standard), indicating that carbon aerogel CAPNix is ​​a mesoporous material with an obvious mesoporous structure. Without nickel, carbon aerogel CAP has the smallest specific surface area and total pore volume. The specific surface area of ​​carbon aerogel CAPNix gradually increases with the increase of nickel content, from 16.2m 2 / g increased to 235.5m 2 / g, and the total pore volume also increased from 0.009cm 3 / g increases to 0.237cm 3 / g, indicating that the aggregation of carbon aerogel skeletons gradually weakens with the increase of nickel content, and has a more developed pore structure, which is consistent with the CAPNix electron microscopy image ( Figure 2 d-2g) results are consistent. Figure 3 Figure i shows the pore size distribution curve of carbon aerogel. The pore size distribution range of carbon aerogel is significantly broadened with the increase of nickel content, and the number of pores with different pore sizes is also greatly increased. The high specific surface area and developed pore structure help to improve the electromagnetic shielding effectiveness of the material.

[0115] 3. Electromagnetic shielding performance of the prepared samples

[0116] Figure 4 This is the electromagnetic interference shielding effect test diagram of the sample. Figure 4As shown in a, the carbon aerogels CAPNix have good electrical conductivity, which is mainly because the aerogels have a good degree of graphitization after high-temperature carbonization, and nickel nanoparticles also promote the conductivity of carbon aerogels. With the increase of nickel content, the conductivity shows a trend of first increasing, then decreasing, and then increasing. In the absence of Ni, the aerogel AAP is carbonized and aggregated by polyvinyl alcohol under high-temperature pyrolysis, so that the alkali lignin carbon particles coated therein are in close contact to form a good conductive network, which makes the carbon aerogel CAP have a good electrical conductivity of 365.8S / m. With the increase of nickel content, the carbon aerogel CAPNi 0.5 The electrical conductivity of carbon aerogels further increased (437.9S / m), mainly because the closely contacted lignin carbon particles and nickel nanoparticles jointly promoted the improvement of electrical conductivity. 1.5 The conductivity of carbon aerogel CAPNi2 decreases significantly, mainly because the pore structure of carbon aerogel expands significantly with the increase of nickel content, which greatly weakens the aggregation phenomenon after PVA carbonization and reduces the contact between lignin carbon, thereby weakening the conductive properties of carbon aerogel. When the addition amount of NiCl2·H2O is 2g, the conductivity of carbon aerogel CAPNi2 has an upward trend, which is because the high nickel content promotes the formation of the conductive network of carbon aerogel. However, considering the cost of raw materials and the impact on the overall performance of the finished product, it is necessary to control the amount of soluble nickel salt added.

[0117] Figure 4 b, 4d show the EMI SE of carbon aerogel CAPNix in the band 8.2-12.4GHz. Without adding Ni, the EMI SE of carbon aerogel CAP can reach 77dB. The main reason is that CAP has high conductivity and dense tubular structure, which makes it have good electromagnetic shielding effectiveness. With the increase of Ni content, the change of carbon aerogel EMI SE is similar to that of conductivity, showing a trend of first increasing, then decreasing and then increasing. 0.5 It has the highest EMI SE of 108dB and reaches the military shielding level. This is mainly due to the carbon aerogel CAPNi 0.5 It has the highest electrical conductivity. In addition, the addition of nickel promotes the magnetic conductivity and pore structure of carbon aerogel. 0.5 With a higher specific surface area and total pore volume, the reflection and scattering paths of electromagnetic waves inside it are increased, making carbon aerogel CAPNi 0.5 The electromagnetic shielding performance of carbon aerogels CAPNi1 and CAPNi 1.5 The EMI SE of carbon aerogels showed a gradual downward trend, which was due to the obvious downward trend of the electrical conductivity of carbon aerogels, especially CAPNi 1.5Although the developed pore structure and good magnetic conductivity contribute to electromagnetic loss, the electrical conductivity still plays a dominant role, resulting in carbon aerogels CAPNi1 and CAPNi 1.5 The electromagnetic shielding effectiveness value is weaker than CAPNi 0.5 Compared with CAPNi1, CAPNi 1.5 The conductivity dropped by about 49%, from 353.2S / m to 180S / m, and the specific surface area increased by about 150%, from 54.1S / m to 136.3S / m. With the joint promotion of specific surface area and magnetic permeability, EMI SE only dropped by about 8%, indicating that high specific surface area and magnetic permeability also contribute to the improvement of electromagnetic shielding effectiveness. 1.5 The conductivity of carbon aerogel CAPNi2 increased slightly. At the same time, carbon aerogel CAPNi2 has a more developed pore structure and higher magnetic permeability than other samples, which makes the electromagnetic shielding performance of carbon aerogel better than CAPNi 1.5 The EMI SE of the carbon aerogel CAPNix prepared in the present invention exceeds that of most previously reported materials, including naturally derived materials and conductive polymer composites containing fillers such as carbon nanotubes, AgNS (silver nanowires), rGO (reduced graphene oxide) and Mxene (two-dimensional transition metal carbide or nitride materials).

[0118] The reflection coefficient (R), absorption coefficient (A) and transmission coefficient (T) are often used to evaluate the shielding mechanism of electromagnetic shielding materials against electromagnetic waves, and respectively represent the shielding ability of the sample against reflection, absorption and transmission of electromagnetic waves. Figure 4 As shown in Figure c, the T values ​​of carbon aerogel CAPNix all tend to 0, indicating that most electromagnetic waves are effectively shielded. The R coefficients of carbon aerogels are all higher than A, indicating that all carbon aerogels are highly reflective materials. Figure 4 As shown in Figure d, regardless of the Ni content, the SEA value of carbon aerogel CAPNix is ​​always higher than the SER value, so the absorption mechanism plays an important role in this process.

[0119] Figure 5The electromagnetic shielding mechanism of the carbon aerogel CAPNix prepared by the present invention is shown. The figure expresses the shielding process of electromagnetic waves passing through the carbon aerogel: when the electromagnetic wave encounters the surface of the carbon aerogel with high conductivity, a small part of the electromagnetic wave is directly reflected due to impedance mismatch, thereby generating reflection loss; when the remaining majority of the electromagnetic wave enters the interior of the carbon aerogel, the electromagnetic wave generates multiple reflections and scatterings in the developed pore structure, and interacts with the high-density mobile carriers to generate conduction losses, so that the electromagnetic wave energy is converted into heat energy. There is a heterogeneous interface between the graphitized part and the defective structure in the carbon aerogel, and the interface polarization phenomenon also promotes the attenuation of electromagnetic waves. In addition, the uniformly distributed magnetic Ni nanoparticles can also become an effective electromagnetic wave loss point, converting part of the electromagnetic wave into heat energy through magnetic loss, thereby increasing the absorption loss of electromagnetic waves. Therefore, under the synergistic effect of high conductivity, developed pore structure, heterogeneous interface and good magnetic conductivity, the carbon aerogel CAPNix prepared by the present invention has excellent electromagnetic shielding performance.

[0120] 4. Joule Heating Performance of Prepared Samples

[0121] Figure 6 This is the Joule heating performance test diagram of the sample. Figure 6 a shows the surface temperature change curve of carbon aerogel CAPNix under 1.5V voltage. After power is turned on, the surface temperature of each carbon aerogel rises rapidly and reaches equilibrium in a short time. As the pore volume increases, the surface temperature of each carbon aerogel decreases. The possible reason is that the larger pore volume reduces the density of the carbon aerogel, thereby reducing the thermal conductivity. 0.5 They all have a relatively high surface temperature, which is greater than 180°C under a voltage of 1.5V. Figure 6 b is carbon aerogel CAPNi 0.5 Surface temperature curves under different voltages. As the applied voltage increases, the carbon aerogel CAPNi 0.5 The surface temperature of the carbon aerogel CAPNi 0.5 Under the action of 2V voltage, the surface temperature can reach 272℃, which has excellent electrothermal conversion performance. Figure 6 As shown in c, carbon aerogel CAPNi 0.5 Temperature change and U 2 There is a linear relationship, with a correlation coefficient of up to 0.99, which conforms to Joule's law; in addition, carbon aerogel CAPNi 0.5 With a higher slope K value (58.2±3.5), a higher Joule heating effect can be achieved at a lower voltage, further indicating that carbon aerogel CAPNi 0.5 It has the potential to prepare high-performance electric heaters. Figure 6d shows carbon aerogel CAPNi 0.5 The surface temperature changes when the input voltage changes step by step. When the applied voltage increases or decreases, the carbon aerogel CAPNi 0.5 It responds quickly and adjusts the surface temperature, showing high sensitivity and excellent electrothermal conversion performance. 0.5 The heating stability of the electric heater under constant supply voltage conditions is studied by long-term heating, such as Figure 6 As shown in Figure e, when the applied voltage is 1.5V, the surface temperature can remain relatively stable within 40min, and the temperature remains constant at around 184℃, indicating excellent heating stability and reliability.

[0122] The above test results show that the carbon aerogel CAPNix prepared in the present invention has excellent electrical conductivity and can be used to prepare a high-performance electric heater by utilizing the Joule heating effect.

[0123] 5. Electromagnetic interference shielding application of the prepared samples

[0124] Figure 7 Demonstrated electromagnetic shielding experiment for Tesla coil, showing the excellent electromagnetic shielding performance of CAPNix. Figure 7 As shown in a, when the LED lamp is close to the powered Tesla coil, the high-frequency electric field in the Tesla coil generates electromagnetic radiation, which provides sufficient energy for the LED lamp and lights up the LED lamp. Figure 7 As shown in Figure b, inserting a log between the Tesla coil and the LED light has no significant effect on the brightness of the LED light, indicating that the electromagnetic shielding effect of natural wood is poor. Figure 7 As shown in Figure c, after the carbon aerogel CAPNix prepared in the embodiment of the present invention is inserted into the same position, the LED lamp is immediately extinguished. The reason is that the excellent electromagnetic shielding performance of the carbon aerogel CAPNix prevents the Tesla coil from outputting energy to the LED lamp through the electromagnetic field.

[0125] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A PVA@alkali lignin-based carbon aerogel, characterized in that: The raw material components include: Alkali lignin, polyvinyl alcohol, soluble nickel salt, water; Among them, the mass ratio of alkali lignin to polyvinyl alcohol is (1-2):1, the mass ratio of alkali lignin to water is 1:(40-60), and the mass ratio of soluble nickel salt to water is (0-4):

300.

2. The PVA@alkali lignin-based carbon aerogel according to claim 1, characterized in that: The mass ratio of the soluble nickel salt to water is (0-2):

300.

3. The PVA@alkali lignin-based carbon aerogel according to claim 2, characterized in that: The mass ratio of the soluble nickel salt to water is (0-1):

300.

4. The PVA@alkali lignin-based carbon aerogel according to claim 1, characterized in that: The soluble nickel salt is NiCl2·6H2O or NiSO4·7H2O.

5. The PVA@alkali lignin-based carbon aerogel according to claim 1, characterized in that: The PVA@alkali lignin-based carbon aerogel has a tubular pore structure inside.

6. A method for preparing PVA@alkali lignin-based carbon aerogel according to any one of claims 1 to 5, characterized in that: The steps include: S1. Add alkali lignin into water and stir to mix evenly; S2, adding polyvinyl alcohol and soluble nickel salt to the solution obtained in step S1, stirring and mixing well, and then pouring the mixture into a mold; S3, freeze-drying the mold and the contents in step S2, and obtaining an aerogel after demoulding; S4, placing the aerogel obtained in step S3 in an inert gas atmosphere for carbonization to obtain PVA@alkali lignin-based carbon aerogel.

7. The method for preparing PVA@alkali lignin-based carbon aerogel according to claim 6, characterized in that: In step S3, the freeze-drying process includes directional freezing and drying.

8. The method for preparing PVA@alkali lignin-based carbon aerogel according to claim 6, characterized in that: In step S4, the carbonization process is as follows: heating the temperature to 900-1100° C. at a heating rate of 1-5° C. / min and keeping the temperature for 1-2 hours.

9. The method for preparing PVA@alkali lignin-based carbon aerogel according to claim 6, characterized in that: In the step S2, the temperature of the solution obtained in the step S1 is first raised and controlled at 80-95° C., and then polyvinyl alcohol and a soluble nickel salt are added thereto.

10. Use of the PVA@alkali lignin-based carbon aerogel according to any one of claims 1 to 5 in the fields of electromagnetic shielding materials and electrothermal conversion materials.

Citation Information

Patent Citations

  • Preparation method of carbon aerogel, carbon aerogel and lithium ion capacitor prepared from same

    CN107680833A

  • Manufacturing method of carbon nikel composite aerogel and supercapacitor electrode

    KR1020110075561A

  • Nanoporous carbon foams

    WO2015193336A1

Cited By

  • Lignin-derived carbon aerogel loaded metal nano-enzyme as well as synthesis method and application thereof

    CN121695861A

  • Lignin-derived carbon aerogel supported metal nanoszyme and synthesis method and application thereof

    CN121695861B